Leveraging AI to uncover the effects of pivotal moments in the LIBOR framework and its evolution on the banking sector - Ellouze, NidhalZiadi; Gafsi, Nesrine (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to investigate the impact of significant events related to the London Interbank Offered Rate (LIBOR) scandal and its transition on the U.S. banking sector. The research utilizes multiple linear regression analysis to assess the relationship between the Dow Jones United States Banks Index and various financial variables, including LIBOR rates, gold prices, and the Volatility Index. The analysis covers data from May 2010 to September 2020, processed using Python. The results indicate that LIBOR rates significantly influence the Dow Jones United States Banks Index, particularly during the periods surrounding the LIBOR scandal and its subsequent discontinuation. The findings highlight LIBOR’s critical role in shaping the performance of the banking sector during tumultuous events. Insights from this study provide valuable guidance for financial analysts and policymakers in understanding the dynamics between interest rates and banking sector stability.